Beyond the anterolateral thigh: the descending branch intermuscular septal (DBIS) flap. Issue 5 (1st October 2020) - Hassan, Kareem; Shakir, Afaaf; Jaffe, Jennifer; Howard, Michael
Abstract: The anterolateral thigh flap (ALT) is widely utilized for coverage of a variety of defects across the body, though use of this flap is limited due to the its size and bulky nature. We describe a flap from the descending branch of the lateral circumflex system including the intermuscular septum (DBIS) without use of the perforator for use of an ultra-thin flap for defect closure. A retrospective review of all patients who underwent wound closure with use of the DBIS flap from March 2016 to August 2018 was performed. Data on patient demographics and date on operative time, defect type, defect size, flap size, vessel size, complications and need for revisions were collected. Seven patients were identified who underwent reconstruction with DBIS flap, six patients for ankle defects and one for a scalp defect. Average age of patients was 66 years and average BMI was 28.9. The most common indication for flap coverage was tendon or joint exposure following total ankle arthroplasty. Average flap area was 36cm 2, average operative time with a single team of surgeons was 258 min, and average length of hospital stay was 3.7 days. The DBIS flap is an excellent option for reliable coverage of defects requiring thin, pliable tissue. Advantages of this flap include ease of dissection, relatively short operative time, primary closure of donor site and minimal contour deformity. Disadvantages include need for a skin graft for flap coverage and limited pedicle length. In the reported series, no complications were reported.